2009
DOI: 10.1515/jpm.2009.036
|View full text |Cite
|
Sign up to set email alerts
|

Evidence to support that spontaneous preterm labor is adaptive in nature: neonatal RDS is more common in “indicated” than in “spontaneous” preterm birth

Abstract: Objectives: The onset of preterm labor has been proposed to have survival value and to be adaptive in nature. This hypothesis would predict that induced preterm birth may be associated with higher rates of complications than spontaneous preterm birth. The purpose of this study was to determine if there is a difference in the frequency of neonatal respiratory distress syndrome (RDS), the most common neonatal complication, according to the etiology of preterm birth (e.g., preterm labor wPTLx, preterm PROM, or pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 27 publications
1
26
1
1
Order By: Relevance
“…These risks are thought to be associated with both gestational age and biological factors associated with the preterm birth, including PPROM 25 , however, immediate delivery does not appear to improve outcomes in preterm neonates and may exacerbate the risks of prematurity because of birth in the absence of labor and earlier gestational age. Although expectant management in a potentially hostile intrauterine environment should be avoided, in a mother who remains well, with no evidence of clinical chorioamnionitis, expectant management provides an opportunity for spontaneous labor to develop and for adaptive changes to occur in the neonate resulting in decreased risk of neonatal respiratory illness 26 . For some neonates, expectant management may also result in delivery at a substantially older gestational age.…”
Section: Discussionmentioning
confidence: 99%
“…These risks are thought to be associated with both gestational age and biological factors associated with the preterm birth, including PPROM 25 , however, immediate delivery does not appear to improve outcomes in preterm neonates and may exacerbate the risks of prematurity because of birth in the absence of labor and earlier gestational age. Although expectant management in a potentially hostile intrauterine environment should be avoided, in a mother who remains well, with no evidence of clinical chorioamnionitis, expectant management provides an opportunity for spontaneous labor to develop and for adaptive changes to occur in the neonate resulting in decreased risk of neonatal respiratory illness 26 . For some neonates, expectant management may also result in delivery at a substantially older gestational age.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of acute histologic chorioamnionitis (acute-HCA) on the development of respiratory distress syndrome (RDS) is still controversial [2]. Acute-HCA is known to be associated with a decreased risk of RDS [3,4], but some human studies do not show this relationship [5,6]. Moreover, no study about the relationship between intra-amniotic inflammation (IAI) and the development of RDS has been reported in human pregnancy, although intra-amniotic injection of inflammatory cytokines and endotoxin in animal model shows an increase in markers that would be considered to be associated with decreased RDS (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In animal studies, intra-amniotic administration of endotoxin or inflammatory cytokine accelerated lung maturation by increasing the production of airway surfactant and improving lung gas exchange, which has been suggested as the mechanism by which antenatal corticosteroids act to promote functional maturation of the fetal lung [18][19][20][21][22][23][24]. Recent studies suggest that chorioamnionitis is associated with the decreased risk of neonatal respiratory distress syndrome, thereby supporting the theory that pulmonary maturation is accelerated in the presence of antenatal inflammation [14,[25][26][27][28][29][30]. Increased endogenous cortisol levels have been suggested as the possible mechanism for this relationship, since cortisol can increase surfactant synthesis in the presence of inflammation as well as increase pulmonary fluid clearance and subsequent gas exchange in the presence of MMPs and neutrophils [25].…”
Section: Inflammation and Respiratory Morbidity In Singleton Pregnancymentioning
confidence: 87%
“…The precise reason for this difference is not well understood, although it has been shown that the presence of inflammation reduces the risk of respiratory morbidity in singleton pregnancies [14]. We postulate that first twins are exposed to higher levels of inflammatory mediators than second twins, and that this may be true throughout pregnancy and not only at term when the cervix is effaced and dilated thereby allowing for ascending infection and inflammation.…”
Section: Introductionmentioning
confidence: 89%